2020
DOI: 10.2807/1560-7917.es.2020.25.17.2000556
|View full text |Cite|
|
Sign up to set email alerts
|

Early experience of an infectious and tropical diseases unit during the coronavirus disease (COVID-19) pandemic, Florence, Italy, February to March 2020

Abstract: We analysed the first 84 coronavirus disease (COVID-19) patients hospitalised in an infectious and tropical disease unit in Florence, Italy, over 30 days after the start of the COVID-19 outbreak in Italy. A 12% reduction in the rate of intensive care unit transfer was observed after the implementation of intensity care measures in the regular ward such as increasing the nurse/patient ratio, presence of critical care physicians and using high flow nasal cannulae oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 8 publications
0
37
0
7
Order By: Relevance
“…Four studies were excluded due to unavailability of the full-text. Finally, 56 papers ( [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ) entered into meta-analysis for primary outcomes (mortality and ICU admission) and 198 papers [ 16 , 18 , [21] , [22] , [23] , [24] , [25] , [26] ,…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were excluded due to unavailability of the full-text. Finally, 56 papers ( [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ) entered into meta-analysis for primary outcomes (mortality and ICU admission) and 198 papers [ 16 , 18 , [21] , [22] , [23] , [24] , [25] , [26] ,…”
Section: Resultsmentioning
confidence: 99%
“…For cohorts in China reporting on hospitalised patients, the prevalence of COPD has ranged from 0 to 10% ( table 1 ) [ 10 41 ]. As data from other nations have trickled in, the figures for COPD amongst hospitalised COVID-19 patients appear to be similar, with estimates in New York City ranging from 2.4 to 14% [ 42 45 ] and in Italy ranging from 5.6 to 9.2% [ 46 48 ]. Data from ICU-only cohorts, however, have been more variable.…”
Section: Is Copd a Risk Factor For Covid-19?mentioning
confidence: 96%
“…As a confirm of this National panorama, in a large cohort of more than 1500 patients of the Lombardy Region admitted to ICUs, men represented more than 80% of the patients just after 40 years of age [ 12 ]. In Florence, the COCORA multidisciplinary group found that hospitalized patients were prevalently males (65.5% vs 34.5%, p 0.045) and a strikingly majority were ICU-transferred (87.5% vs 12.5%) [ 13 ]. Thus, within Italy, severe clinical course and deaths from COVID-19 are mainly observed among older, male patients confirming lower rates of severe disease among women and younger individuals overlapping data initially described in China [ 14 ].…”
Section: Main Textmentioning
confidence: 99%